2014
DOI: 10.1371/journal.pone.0103323
|View full text |Cite
|
Sign up to set email alerts
|

Slik and the Receptor Tyrosine Kinase Breathless Mediate Localized Activation of Moesin in Terminal Tracheal Cells

Abstract: A key element in the regulation of subcellular branching and tube morphogenesis of the Drosophila tracheal system is the organization of the actin cytoskeleton by the ERM protein Moesin. Activation of Moesin within specific subdomains of cells, critical for its interaction with actin, is a tightly controlled process and involves regulatory inputs from membrane proteins, kinases and phosphatases. The kinases that activate Moesin in tracheal cells are not known. Here we show that the Sterile-20 like kinase Slik,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 86 publications
0
10
1
2
Order By: Relevance
“…3A,B). Although there is evidence that actin matrices underlie organization of both the basal and apical plasma membranes in terminal cells (Gervais and Casanova, 2010;JayaNandanan et al, 2014;Levi et al, 2006;Schottenfeld-Roames et al, 2014;Ukken et al, 2014), we do not observe such matrices, probably because our fixation methods do not preserve these particular cytoskeletal elements. The features we observe are consistent with previous reports of tracheolar ultrastructure, observed in Drosophila and other insects fixed using standard chemical techniques, but with an increased resolution of cellular membranes (Levi et al, 2006;Manning and Krasnow, 1993;Noirot and Noirot-Timothee, 1982;Snelling et al, 2011).…”
Section: Resultscontrasting
confidence: 72%
“…3A,B). Although there is evidence that actin matrices underlie organization of both the basal and apical plasma membranes in terminal cells (Gervais and Casanova, 2010;JayaNandanan et al, 2014;Levi et al, 2006;Schottenfeld-Roames et al, 2014;Ukken et al, 2014), we do not observe such matrices, probably because our fixation methods do not preserve these particular cytoskeletal elements. The features we observe are consistent with previous reports of tracheolar ultrastructure, observed in Drosophila and other insects fixed using standard chemical techniques, but with an increased resolution of cellular membranes (Levi et al, 2006;Manning and Krasnow, 1993;Noirot and Noirot-Timothee, 1982;Snelling et al, 2011).…”
Section: Resultscontrasting
confidence: 72%
“…Support for phosphorylation cycling-dependent local stabilization at the apical plasma membrane comes from a study by Viswanatha and colleagues, which showed that localized kinase activity at the apical membrane of microvilli-containing mammalian cells is able to restrict ezrin to the apical plasma membrane (Viswanatha et al, 2012). Similar polarized kinase activity was shown to restrict Moesin activity to the apical cortex of tracheal cells in Drosophila (Ukken et al, 2014).…”
Section: Discussionmentioning
confidence: 94%
“…2A). Signaling leads to many changes in cytoskeletal organization [3438] (Fig. 2A), and these cytoskeletal changes may be important for the ultimate formation of seamless tubes.…”
Section: Examples Of Seamless Tubesmentioning
confidence: 99%
“…Defects in branch outgrowth and lumen outgrowth are often coupled, but some mutations disrupt this coordination, and lead to long, convoluted lumens out of register with the basal membrane, or to multiple separate and disorganized lumens. Such mutants affect cytoskeletal organization and/or specific trafficking regulators, such as Rab35 or Cdc42, that may direct vesicles to appropriate locations for membrane fusion [38, 50, 70, 75, 8082]. …”
Section: Seamless Tube Shaping and Maintenancementioning
confidence: 99%
See 1 more Smart Citation